Pembelajaran Membaca Al-Qur’an Menggunakan Metode Iqro’ untuk Mengurangi Angka Buta Huruf Al-Qur’an - Rappe; Munawwir, Ahmad; Mappasiara; Syarifuddin, Erlangga; Hasriati (KHIDMAH: Jurnal Pengabdian Masyarakat, 2023)
Society is the pioneer, determinant of progress, and the welfare of a state and nation, therefore the government of a country must pay attention to the welfare of the community, especially the young generation that has just grown up among the community. It is this young generation that will determine the fate of the nation and state in the future, because today's youth are the leaders of the future. Our country, Indonesia, has a lot of diversity in religion, culture, and so on, Indonesia is also a religious country, it can be seen in the ideology of the nation, namely Pancasila, in the first principle which reads "Belief in One God", however, many Indonesian people who are the majority of adherents of Islam cannot read the Qur'an, or in other words they are illiterate al-Qur'an with a percentage of 65% of 223 million Muslims unable to read the Qur'an, and this is a serious problem for Muslims in Indonesia. The purpose of this service is to provide guidance and learning to the children of the nation's generation to read the Qur'an properly and correctly, using the Iqro' method which refers to the "Child Centered" education pattern which provides the widest possible opportunity for each learner to develop optimally according to ability, to improve the quality of the younger generation on the religious side in accordance with the first principle of Pancasila, and reduce the number of Qur'an illiteracy in Indonesia.